Molecular Diagnosis of Scrub Typhus: Sample and Timing Matter - Nagarajan L Surya; Sania Paul; Susmitha K Perumalla; Karthik Gunasekaran; KPP Abhilash; JAJ Prakash (Zoonoses, 2024)
<!-- named anchor --> Objective: Scrub typhus (ST) is an acute febrile illness caused by Orientia tsutsugamushi. Laboratory tests are needed to confirm the diagnosis when the characteristic eschar is absent. This study aimed to evaluate the performance of 47 kDa qPCR using clotted and EDTA-treated blood among patients with suspected ST <!-- named anchor --> Methods: Clotted blood samples from 284 inpatients (IPs) and EDTA-treated blood samples from 194 outpatients (OPs) with suspected scrub typhus were collected from patients who were blood culture- and malaria-negative. ST IgM ELISA and 47 kDa qPCR were performed for detection of ST infections. <!-- named anchor --> Results: Among the IPs (n=284) and OPs (n=194), 41% and 63% were confirmed to have ST based on the case definition, respectively; the mortality rate was 1%. The 47 kDa qPCR sensitivity of the buffy coat (65.6%) was greater compared to clotted blood (37.1%). PCR was more likely to be positive in the 1st week of the illness; IgM ELISA positivity increased after the 5th day of the illness. <!-- named anchor --> Conclusion: The type of sample and the time of sample collection have a role in the diagnosis of ST. These preliminary results need to be confirmed by prospective multicentric studies.